Chloride intracellular channel 1 (CLIC1) contributes to modulation of cyclic AMP-activated whole cell chloride currents in human bronchial epithelial cells - Liu, Bo; Billington, Charlotte K.; Henry, Amanda P.; Bhaker, Sangita K.; Kheirallah, Alexander K.; Swan, Caroline; Hall, Ian P. (Wiley Open Access, 2018)
Chloride channels are known to play critical physiological roles in many cell types. Here we describe the expression of anion channels using RNA Seq in primary cultures of human Bronchial Epithelial Cells (hBECs). Chloride intracellular channel (CLIC) family members were the most abundant chloride channel transcripts, and CLIC1 showed the highest level of expression. In addition, we characterise the chloride currents in hBECs and determine how inhibition of CLIC1 via pharmacological and molecular approaches impacts these. We demonstrate that CLIC1 is able to modulate cyclic AMP-induced chloride currents and suggest that CLIC1 modulation could be important for chloride homeostasis in this cell type.